Cationic liposomes in mixed didodecyldimethylammonium bromide and dioctadecyldimethylammonium bromide aqueous dispersions studied by differential scanning calorimetry, nile red fluorescence, and turbidity - Feitosa, E.; Alves, F. R.; Niemiec, A.; Oliveira, MECDR; Castanheira, EMS; Baptista, ALF (Amer Chemical Soc, 2006)
The thermotropic phase behavior of cationic liposomes in mixtures of two of the most investigated liposome-forming double-chain lipids, dioctadecyldimethylammonium bromide (DODAB) and didodecyldimethylammonium bromide (DDAB), was investigated by differential scanning calorimetry (DSC), turbidity, and Nile Red fluorescence. The dispersions were investigated at 1.0 mM total surfactant concentration and varying DODAB and DDAB concentrations. The gel to liquid-crystalline phase transition temperatures (T-m) of neat DDAB and DODAB in aqueous dispersions are around 16 and 43 degrees C, respectively, and we aim to investigate the T-m behavior for mixtures of these cationic lipids. Overall, DDAB reduces the T-m of DODAB, the transition temperature depending on the DDAB content, but the T-m of DDAB is roughly independent of the DODAB concentration. Both DSC and fluorescence measurements show that, within the mixture, at room temperature (ca. 22 degrees C), the DDAB-rich liposomes are in the liquid-crystalline state, whereas the DODAB-rich liposomes are in the gel state. DSC results point to a higher affinity of DDAB for DODAB liposomes than the reverse, resulting in two populations of mixed DDAB/DODAB liposomes with distinctive phase behavior. Fluorescence measurements also show that the presence of a small amount of DODAB in DDAB-rich liposomes causes a pronounced effect in Nile Red emission, due to the increase in liposome size, as inferred from turbidity results.